RESILIENSI DAN LOCUS OF CONTROL GURU DAN STAF SEKOLAH PASCA GEMPA - Sudaryono, Sudaryono (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
Abstract Studies related to aspect of resilience of Yogyakarta, an earthquake site, are important. The result of studies can be used to alleviate people from the desperate situation. This research aimed to explore the resilience of the teachers and staffs of the SMU Negeri 1 Pundong based on their locus of control or LOC (internal and external). The subsequent aim was to exploredifferences in psychological aspects that build resilience between internal and external locus of control. Thirty people were recruited as participants, in which 16 of them has internal LOC and 14 had external LOC. IPC scale of Locus of Control based on Levenson and resilience scale were employed as instruments. The resilience scale consisted of seven aspects: emotional regulation, impulse control, empathy,optimism, causal analysis, self-eficency, and reaching-out. It was developed by on Reivich ad Shatte method. Results showed that there was no significant difference in the levels of resilience between internal and external LOC (t= 1.343, p=0.190). the following analysis showed that the two groups(internal and external LOC) differed n two aspects, empathy (t=2.722, p< 0.05) and reaching out (t=2.389, p< 0.05). the meaning and possible causes of the result were discussed. Keywords: resiliency and lotus of control